Rancangan Sistem Pencarian Pasien, Dokter Dan Kamar Pada Rumah Sakit Berbasis Web Menggunakan Multi DBMS - M.TI, Indera (Jurnal Informatika, 2010)
The information in a hospital is needed by patients or visitors. This web-based system built to facilitate search of information about a patient who was treated in certain hospitals and in certain rooms. If a patient will be seeing a particular doctor, this application also provides a list of doctors who practice in certain hospitals. The system is designed by using three DBMS that represents the three hospitals. With this system, although it has three different databases, but still can be integrated in a single web application, so users do not need to open many web applications for the same purpose. Keyword : Search engine, Multi DBMS, database